HUBUNGAN GAYA MENGAJAR GURU DENGAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN KIMIA DI KELAS XI MIPA SMA NEGERI 4 KOTA BENGKULU - Nailawati; I Nyoman Candra; Wiwit (ALOTROP, 2026)
Teaching style is one of the important factors that influence student learning motivation in the learning process. This study aims to determine the categories of teaching styles and student learning motivation, as well as the relationship between the two in chemistry learning in class XI MIPA at SMA Negeri 4 Kota Bengkulu. This study used a correlational descriptive method by distributing questionnaires to 220 respondents. The results showed that (1) the teaching style category of teachers in data group A was in the high category with a percentage of 75.15%, and in data group B, it was in the high category with a percentage of 76.67%. Teachers' teaching styles were analyzed based on indicators of voice variation, focus of attention, teacher silence, eye contact, body movements and facial expressions, and position changes. (2) The category of student learning motivation in data group A was in the high category with a percentage of 73.35%, and in data group B, it was in the high category with a percentage of 73.05%. Student learning motivation was analyzed based on indicators of desire and willingness to achieve, encouragement and need to learn, hopes and aspirations, independence in learning, perseverance in learning, and resilience in facing difficulties. (3) There was a significant positive relationship between teaching style and student learning motivation, with a low level of relationship strength in data group A and a moderate level of relationship strength in data group B.